Chelating effect of silver nitrate by chitosan on its toxicity and growth performance in broiler chickens - Doriane, Yemdjie Mane Divine; Raphaël, Kana Jean; Augustave, Kenfack; Lavoisier, Fonou Tadiesse; Ruben, Ngouana Tadjong; Narcisse, Vemo Bertin; Alexis, Teguia; Amir, Meimandipour (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to investigate the chelating effect of silver nitrate (AgNO3) by chitosan on growth performances, hematological and biochemical parameters, and the histopathological structure of the liver and the kidney in broiler chicken. Materials and methods: A total of 192 day-old Cobb 500 strain chicks were randomly assigned to 3 treatments of 64 chicks each. Control group was fed on basal diet without supplement (R0) and the two others groups were fed on rations supplemented with 10 mg of unchelated (RAg) or chelated (RCs-Ag) AgNO3 per Kg of feed, respectively. Parameters that have been studied consisted of feed intake, weight gain, blood and serum biochemical, and histopathological analyses of liver and kidney. Results: Results revealed that chelation of AgNO3 by chitosan did not have any effect on growth performances and hematological parameters in chicken. However, chelated and unchelated AgNO3 increased the serum content in triglyceride, and cholesterol and decreased the serum content in creatinin, albumin and alanine aminotransferase (ALAT). Chelating AgNO3 with chitosan prevented and corrected the toxicity induced on the histological structure of liver and kidney. Conclusion: Chitosan can be used as a chelating agent to alleviate the harmful effects of AgNO3 as silver ion for poultry. http://doi.org/10.5455/javar.2017.d210 XML PubReader